2018
DOI: 10.1007/s10792-018-0912-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chalazion surgery on intraocular pressure and corneal topography

Abstract: To the best of our knowledge, this is the first report to suggest that IOP and CKI are decreased after the removal of upper eyelid chalazion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In several previous studies, it was revealed that the chalazion resulted in changes in corneal astigmatism and aberrations due to the effect of mechanical compression (14)(15)(16). In addition, it has been reported that chalazion may cause an increase in intraocular pressure and that a decrease in intraocular pressure would be achieved after excision (17). It has been stated that lesions on the upper eyelid, involving the central eyelid and that are >5 mm, have a greater effect on corneal astigmatism and aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies, it was revealed that the chalazion resulted in changes in corneal astigmatism and aberrations due to the effect of mechanical compression (14)(15)(16). In addition, it has been reported that chalazion may cause an increase in intraocular pressure and that a decrease in intraocular pressure would be achieved after excision (17). It has been stated that lesions on the upper eyelid, involving the central eyelid and that are >5 mm, have a greater effect on corneal astigmatism and aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Some common eye diseases, such as congenital ptosis [ 11 ], eyelid hemangioma [ 12 ], allergic conjunctivitis [ 13 ] and bad eye rubbing habit [ 14 ], can cause astigmatism in children. It has been confirmed that large chalazions in the middle- upper eyelid could cause corneal astigmatism [ 15 18 ]. In an elderly man with farsightedness due to a chalazion mass in the middle-upper right eyelid, visual acuity returned to normal after the mass was removed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the relationship between chalazion and astigmatism have focused on corneal astigmatism rather than total astigmatism [ 15 , 17 , 18 ]. However, these studies have reported single-site masses, mainly larger masses in the middle-upper eyelid, and lack comprehensive studies of all site [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe cases can cause eyelid eversion, eye deformities, and if secondary infections occur, they can develop into a stye [4][5][6] . Chalazion has a high incidence in children, and its treatment usually includes surgical and non-surgical methods [7][8] . The operation often needs to be performed under general anesthesia, which will cause many problems for children and parents.…”
Section: Introductionmentioning
confidence: 99%